Privacy Rights in the Digital Age - Kirtley, Jane E.; Shally-Jensen, Michael (Grey House Publishing, 2019)
Discusses the practical, political, psychological, and philosophical challenges of technological advances have changed the landscape of traditional notions of privacy.